2022
DOI: 10.1155/2022/9151169
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Oxidative Phosphorylation Complexes and Mitochondrial Mass in Pediatric and Adult Inflammatory Bowel Disease

Abstract: Introduction. Inflammatory bowel disease (IBD), which includes Crohn’s disease (CD) and ulcerative colitis (UC), is a multifactorial intestinal disorder but its precise etiology remains elusive. As the cells of the intestinal mucosa have high energy demands, mitochondria may play a role in IBD pathogenesis. The present study is aimed at evaluating the expression levels of mitochondrial oxidative phosphorylation (OXPHOS) complexes in IBD. Material and Methods. 286 intestinal biopsy samples from the terminal ile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…However, prior studies relied on transcriptomes from whole biopsies taken from actively inflamed tissue, 35 whereas, we focused on epithelium from locations that were inflammation-adjacent. Furthermore, the crypt orientation in immunohistological staining for OXPHOS complexes presented in other reports, 35 , 36 does not consistently offer insight into the crypt base. We utilized stem cell-biased culture conditions, which may have revealed transcriptional events that would remain unnoticed when examining the intestinal epithelium broadly.…”
Section: Discussionmentioning
confidence: 63%
“…However, prior studies relied on transcriptomes from whole biopsies taken from actively inflamed tissue, 35 whereas, we focused on epithelium from locations that were inflammation-adjacent. Furthermore, the crypt orientation in immunohistological staining for OXPHOS complexes presented in other reports, 35 , 36 does not consistently offer insight into the crypt base. We utilized stem cell-biased culture conditions, which may have revealed transcriptional events that would remain unnoticed when examining the intestinal epithelium broadly.…”
Section: Discussionmentioning
confidence: 63%
“…Choline dehydrogenase (CHDH) as the mitochondrial enzyme is responsible for catalyzing the dehydrogenation of choline into betaine aldehyde and regulates mitophagy by recruiting SQSTM1 and LC3 to the mitochondria [ 29 ]. In recent years, studies have shown the importance of mitophagy within the intestinal epithelium during UC pathogenesis [ 16 , 30 , 31 ]. CHDH also primarily contributes to biological processes such as inflammatory response, vascular lesion, metabolic process and cell cycle [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The samples were classified according to a previous study by Schneider et al [ 83 ]. Patients with macroscopically and histologically proven IBD were assigned to the study group.…”
Section: Methodsmentioning
confidence: 99%
“…If the results of the colonoscopy excluded UC and CD, they were appointed as controls. The analysis was conducted by the pathologists using a histologic severity score (HSS) in accordance with the study by Schneider et al [ 83 ]. Zero to three points were given in each of the categories of crypt architecture, signs of acute inflammation, signs of chronic inflammation and regeneration of the epithelium, resulting in a score range of 0–12.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation